A Readability Level of Reading Materials for Vocational High School Students in Lombok, NTB - Kamarudin Kamarudin; Nanang Sugianto (Jurnal Paedagogy, 2020)
This study aims to find out a readability level of reading materials for the students in one of the Vocational High Schools in Lombok, NTB using Cloze procedure, Flesh formula, and Fry Graph formula for the 12th grade. This study is a descriptive quantitative research. The sample of the study were 32 students using English textbooks presented for 12th graders in one of Vocational High Schools in Lombok, NTB. There were three genres performed; descriptive, recount, and narrative text. For the Flesh formula, and Fry Graph, the researcher’s observations were as the instrument of the study, meanwhile, for Cloze procedure, a test was employed to collect the data needed. The data was analyzed quantitatively described in the form of numerical description and percentage. The result revealed that analyzing the readability level through Cloze procedure was 42%, designated that the reading materials were instructional/assisted to read, and Flesh formula was 82.7%, indicated that the reading materials were easily understandable by the students, and Fry Graph formula showed that the reading materials were readable for the students. Thus, reading materials for students in one of the Vocational High Schools in Lombok, NTB was readable for 12th graders to read.